Effect of Curcumin-Nanoemulsion Associated with Photodynamic Therapy in Cervical Carcinoma Cell Lines - De Matos, Renata Prandini Adum [UNESP]; Calmon, Marilia Freitas [UNESP]; Amantino, Camila Fernanda; Villa, Luisa Lina; Primo, Fernando Lucas [UNESP]; Tedesco, Antonio Claudio; Rahal, Paula [UNESP] (Wiley, 2018)
Cervical cancer is the fourth cause of cancer death in women. Curcumin has antineoplastic properties. Furthermore, curcumin may be used as a photosensitizing agent in Photodynamic Therapy. This study aimed to investigate the effects of Photodynamic Therapy in cellular viability using curcumin-nanoemulsion as a photosensitizing drug in cervical carcinoma cell lines. The empty nanoemulsion presented very low cytotoxicity in all cell lines analyzed. Additionally, the incubation with curcumin-nanoemulsion at 20 μM of curcumin showed more than 80% of cell viability for cell lines. Nanoemulsions were shown to be internalized inside cells by fluorescence microscopy and were observed in the intracellular environment for up to 36 hours after incubation with cell lines. In addition, after the Photodynamic Therapy we observed a high phototoxic effect of the curcumin-nanoemulsion with less than 5% of viable cells after irradiation. This was accompanied by an increase in caspase-3/caspase-7 activities after cell treatment with curcumin-nanoemulsion and Photodynamic Therapy, suggesting cell death by apoptosis. We conclude that the curcumin-nanoemulsion formulation behaves as a photosensitizing drug in Photodynamic Therapy and shows potential as an alternative treatment to cervical lesions using an endoscopic diode fiber laser setup for in situ activation or cavity activation using a diffuse fiber delivery system.